THE USE OF CODE-SWITCHING IN HIGHER EDUCATION: WHAT LECTURERS DO AND HOW THEIR STUDENTS PERCEIVE ABOUT IT - Wawan Setiawan; Ade Surista (Wiralodra English Journal, 2024)
The present study aims to describe the rationale of the practice of code-switching, explain to what extent it was used, and explore the students' perspectives on this practice. Through open and closed questionnaires shared with the students majoring in English departments and the lecturers at the School of Foreign Language JIA, the results show that most of the lecturers admitted their use of code-switching in their class, which mainly helped students understand the materials more easily. The code-switching was not only used in the areas of curriculum access but also classroom management and interpersonal relations. In line with this, the majority of the students confirmed a positive view towards this practice since it could assist their learning process and confidence level, so there is a correlation between the rationale of the use of code-switching and the students’ perspectives. Thus, the results suggest the practice of code-switching could be employed by lecturers in the EFL contexts in higher education to enhance students’ understanding towards the lessons.